A full-scale exercise for preparedness for uncertain and novel chemical hazards with pediatric casualties: project PUNCH - Kane, Ashley; Cahan, Lea Ohana Sarna; Abelanes, Sally-Mae; Adnan, Mohd Syafwan; Woodward, Christina; Tin, Derrick; Labib, Ibrahim; Issa, Fadi; Voskanyan, Amalia; Weiner, Debra (Cambridge University Press, 2023)
Introduction: In 2022, the Harvard/Beth Israel Deaconess Disaster Medicine Fellowship conducted a full-scale exercise (FSX) with the dual mission of 1) training Disaster Medicine Fellows (DMFs) in exercise design, planning, and execution, and 2) expanding local first responder experience with pediatric casualties in a mixed-method terrorist attack. Method: Project PUNCH (Preparedness for Uncertain and Novel Chemical Hazards) was planned in two stages. A tabletop exercise in the form of a facilitated discussion was conducted in March 2022 with stakeholders from Fire, Emergency Medical Services (EMS), and the Massachusetts HazMat Team.AFSX simulating a combined blast and chemical attack on a family gathering was held in June 2022 at Anna Maria College in Paxton, MA. Results: Fire, EMS, HazMat, LifeFlight, local Police, MA State Police, a local Medical Reserve Corps, and over 40 volunteer victims including 16 pediatric volunteers participated in the FSX. The FSX was a two-hour exercise with a simulated explosion and a secondary drone-deployed dummy-opioid aerosol release. This was the first FSX for the Paxton Region since the coronavirus pandemic began. Planning was conducted by the DMFs between January and June 2022 with the aid of Fellowship faculty and local stakeholders following Homeland Security Exercise and Evaluation Program guidelines. Local and Fellowship leadership with Pediatric expertise were engaged to plan pediatric specific considerations, precautions and safety measures. COVID precaution guidelines were followed. These efforts are detailed in the forthcoming field report. Educational guides for toxidromes and triage and resuscitation of pediatric victims were distributed to first responders. Conclusion: The end outcome was a FSX that trained DMFs in exercise design, planning, and execution, and increased experience of local first responders with the concepts of asymmetric terrorist attacks and comfort with pediatric disaster victims. Multi-agency disaster drills remain an important training tool for preparedness and response to mass casualty events.